Leaders of the pack : girl groups of the 1960s and their influence on popular culture in Britain and America - MacLeod, Sean, 1971- (Rowman and Littlefield, 2015)
"Musician and music historian Sean MacLeod surveys the hundreds of girl groups that appeared not only in the United States but also in Great Britain during the early 1960s. This study corrects the neglect of their critical contribution of popular music history by exploring the social and political climate from which the girl groups emerged and their effect, in turn, on local and national music and culture. MacLeod organizes his argument around seven leading girl groups: The Shirelles, The Crystals, The Ronettes, The Marvelettes, The Vandellas, the Supremes and The Shangri-Las. These seven "sister" groups serve as the basis for a broader look at the many girl groups of the period, offering a roadmap through the work of the many stakeholder--the singers, songwriters, producers, and record labels--that the girl group phenomenon made possible. MacLeod also reviews the significant influence girl groups had on the many male bands of the 1960s, as well as their influence on the post-'60s movements, from punk to new wave, ultimately serving as the template for the girl groups and all-girl bands that emerged in the 1980s. Finally, The Leaders of the Pack brings us to the present as MacLeod compares the original girl groups with female performers of today, drawing lines of connection and contrast between them."--Publisher's description